Parâmetros erosividade da chuva, da enxurrada e da chuva-enxurrada correlacionados com as perdas de solo de um luvissolo - Albuquerque, A. W.; Lombardi Neto, F.; Cataneo, A. [UNESP]; Srinivasan, V. S.; Santos, J. R. (Sociedade Brasileira de Ciência do Solo, 2002)
Simple linear, multiple linear and nonlinear correlations between rainfall, runoff and rainfall-runoff erosivity parameters were studied, as well as soil losses caused by erosive rainfall on a Haplargids. Data were obtained in the period from 1986 to 1990 at the Experimental Station in Sumé, which belongs to the Universidade Federal da Paraíba - UFPB, Paraíba State, Brazil. Individual rainfalls registered in 136 rain gauges were analyzed for the determination of rainfall, runoff and rainfall-runoff erosivity parameters. The runoff volume, single or combined with rainfall characteristics improved the estimated soil losses of individual rainfall significantly. The erosivity parameters for rainfall-runoff a(Vu α I30)b; a(Vu α I5)b; a(EIA)b and runoff a(Vu)b were best fit to estimate soil losses caused by individual storms. The rainfall erosivity parameters that included the product of rainfall volume at a maximum intensity for thirty minutes (VrI30) were the ones that correlated best with soil losses.

Foram estudadas as correlações lineares simples, múltiplas e não-lineares entre os parâmetros erosividade da chuva, da enxurrada e da chuva-enxurrada e as perdas de solo provocadas por chuvas erosivas num Luvissolo. Os dados correspondentes ao período de 1986-1990 foram obtidos na estação experimental de Sumé (PB), pertencente à Universidade Federal da Paraíba - UFPB. Para determinar os parâmetros erosividade da chuva, da enxurrada e da chuva-enxurrada, foram analisadas chuvas individuais registradas em 136 pluviogramas. O volume de enxurrada isolado ou em combinação com características da chuva contribuiu, de forma significativa, para melhorar a estimativa das perdas de solo de chuvas individuais. Os parâmetros erosividade da chuva-enxurrada a(Vu α I30)b; a(Vu α I5)b; a(EIA)b e da enxurrada a(Vu)b foram os melhores estimadores das perdas de solo para chuvas individuais. Dentre os parâmetros da erosividade da chuva, os que melhor se correlacionaram com as perdas de solo foram aqueles que incluíram o produto do volume da chuva pela intensidade máxima em trinta minutos a(VrI30).
Rainfall, runoff, and rainfall-runoff erosivity parameters correlated with soil losses of a haplargids, Paraiba state, Brazil
Keywords: erosão; semi-árido; modelo; erosion; semiarid; models